Providing the Comparability Conditions of Results on Cryopreservation of Mammalian Embryos - Gorbunov, L. V.; Gordienko, E. A. (Problems of Cryobiology and Cryomedicine, 2011)
There was proposed mathematical model of estimation of initial state and efficiency of cryopreservation of mammalian embryos, providing the comparability of the results when using different methods of freezing. It has been shown that initial viability of bovine embryos makes 70â€“100% and depends on physiological state of embryos and their donor. Cryopreservation efficiency of murine and bovine embryos varies from 53 to 95%, which is stipulated by the state of embryo and peculiarities of the methods applied. Taking into account of biological object features and the cryopreservation way (initial state and efficiency of stages) provides the statistical significance of the obtained values P â‰¥ 0.95 with the decrease in the number of mammalian embryos 10 times.